Zootechnical performances and profitability of local breed’s pigs fattened through the application of feed and health technological packages in traditional livestock farms in Casamance, Senegal - Walter Ossebi; Simplice Bosco Ayssiwede; Sodjinin Atchiwassa; Augustin Eric Djettin; Richard Malou; Mariame Diop; Ayao Missohou (Journal of Applied Animal Research, 2023)
This work aims to assess the effects of the application of feed and health technological packages on the zootechnical-economic performance of local breeds pigs in Casamance. It involved 253 young pigs, provided by 44 traditional farms. The feed and health technological package group (FHT) pigs were kept in permanent confinement and fed ad-libitum with a diet containing 15% of dried cashew apple pulp, while the controls and health technological package (HT) pigs were raised in a free-range area and fed in the usual way by the farmers. The zootechnical and economic parameters were collected and processed by ANOVA test and linear regression. The results showed a significant improvement in health status, live body weight, carcass weight of pigs, daily weight gain mean of the pigs in the FHT group compared to the HT and controls (p < 0.05). The production costs of the FHT pigs were lower than those of the HT and control pigs’ groups. They generated on average a gain for the selling in live body weight and a loss for those in carcass weight. The use of feed and health technological packages is advised in pig farming and price incentives are necessary to make the fattening activity sustainable.